Exploration of Constructivist Learning Models in Developing Critical Thinking Skills: A Systematic Literature Review - Nova Pratiwi; Eeng Ahman; Disman Disman; Hari Mulyadi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Critical thinking is vital for academic and professional success in the 21st century. However, many students, particularly in Indonesia, face difficulties in developing higher-order thinking skills. This challenge necessitates effective instructional strategies that promote critical thinking in educational environments. This study employed a Systematic Literature Review (SLR) using the PRISMA protocol to identify and evaluate constructivist learning models that support critical thinking development. A total of 30 empirical studies published between 2015 and 2024 were selected through systematic identification, screening, and inclusion processes. Thematic analysis was conducted to extract insights on the implementation and effectiveness of five constructivist approaches: Problem-Based Learning (PBL), Project-Based Learning (PjBL), Inquiry-Based Learning (IBL), Collaborative Learning (CL), and Discovery Learning (DL). Findings indicate that all five models significantly enhance students’ critical thinking skills. PBL and PjBL were the most frequently studied and demonstrated strong outcomes in problem-solving, analysis, and collaboration. IBL and DL promoted curiosity and autonomous learning, while CL was effective in fostering group discussion and collective problem-solving. Constructivist learning models offer substantial benefits in cultivating critical thinking. However, their effectiveness relies heavily on factors such as institutional support, teacher preparedness, and cultural context. Constructivist approaches are effective pedagogical tools for enhancing critical thinking. Future studies should further investigate model-specific challenges and explore their adaptation in varied educational contexts.